Food Neophobia and Animal Protein Intake in Children Aged 3-5 Years: A Cross-Sectional Study in Indonesia - Khoirunnisa, Novia Tri; Purwanti, Rachma; Nuryanto, Nuryanto; Rahadiyanti, Ayu (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Food neophobia, defined as the avoidance of unfamiliar or familiar foods due to fear and negative perceptions, can significantly influence children’s dietary variety and nutritional adequacy. Previous studies have highlighted inconsistent findings on its relationship with protein intake, yet limited evidence exists in Indonesia. This study aimed to examine the association between food neophobia and animal protein consumption among toddlers aged 3–5 years in Semarang City, Indonesia. An observational analytic study with a cross-sectional design was conducted from May to July 2024. Data were collected through interviews with parents/caregivers using the Child Food Neophobia Scale (CFNS) and a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Statistical analysis applied Chi-Square tests and logistic regression at a 95% confidence level (p < 0.05). A total of 73 toddlers participated in the study. Findings revealed a significant correlation between food neophobia and frequency of dairy product consumption (p < 0.001), with neophobic children being 13.4 times more likely to consume dairy products than food-neutral children. However, no significant associations were observed with the adequacy or frequency of seafood, poultry, or red meat consumption. These findings indicate that while food neophobia may restrict dietary variety, the preference for dairy can serve as a compensatory nutrient source, particularly for calcium and protein, supporting growth and development. In the Islamic perspective, the inclusion of milk as a wholesome and pure food aligns with Quranic teachings, reinforcing family health practices that integrate both nutritional and spiritual well-being.